2021
DOI: 10.1038/s41467-021-26244-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-chemoattractants enhance neutrophil clearance of Staphylococcus aureus

Abstract: The pathogen Staphylococcus aureus can readily develop antibiotic resistance and evade the human immune system, which is associated with reduced levels of neutrophil recruitment. Here, we present a class of antibacterial peptides with potential to act both as antibiotics and as neutrophil chemoattractants. The compounds, which we term ‘antibiotic-chemoattractants’, consist of a formylated peptide (known to act as chemoattractant for neutrophil recruitment) that is covalently linked to the antibiotic vancomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…5 B, quantification revealed that the bacterial abundance in both the 25 mg/ml and 50 mg/ml groups decreased to less than 20% of that in the control group, indicating that the growth of MRSA was suppressed in vivo. As a previous study reported, some antibacterial drugs could improve the recruitment and engulfment of neutrophils in the infection area, which promoted the killing of S. aureus 14 . Therefore, the suppression of MRSA could contribute to the increased phagocytosis and clearance of S. aureus by the increasingly infiltrated inflammatory cells.…”
Section: Resultsmentioning
confidence: 85%
“…5 B, quantification revealed that the bacterial abundance in both the 25 mg/ml and 50 mg/ml groups decreased to less than 20% of that in the control group, indicating that the growth of MRSA was suppressed in vivo. As a previous study reported, some antibacterial drugs could improve the recruitment and engulfment of neutrophils in the infection area, which promoted the killing of S. aureus 14 . Therefore, the suppression of MRSA could contribute to the increased phagocytosis and clearance of S. aureus by the increasingly infiltrated inflammatory cells.…”
Section: Resultsmentioning
confidence: 85%
“…One example is the discovery of “antibiotic‐chemoattractants”, a recombinant antibacterial peptide consisting of vancomycin and pathogen‐associated neutrophil chemoattractant, with the ability to prevent S. aureus infection through targeted activation of the immune system. [ 31 ] In this covalently linked complex, vancomycin functions as a targeting agent with the ability to bind the S. aureus cell wall and kill bacteria, and chemoattractants recruit neutrophils to the surroundings of bacteria, which effectively enhances bacterial clearance. However, the attachment of the two molecules may lead to a significant loss of their own activity, which could lead to poor therapeutic activity, more optimum exploration might be needed.…”
Section: Discussionmentioning
confidence: 99%
“…shown by fusion of an antibiotic-targeting element with an FPR agonist, which enhances neutrophil clearance, providing a viable immunotherapeutic strategy to treat resistant S. aureus infections (Payne et al, 2021).…”
Section: Indications For Fpr2-targeted Therapiesmentioning
confidence: 99%
“…Evidence for FPR2‐targeted therapies for each of these indications has been obtained from exogenous administration of peptides derived from endogenous FPR agonists, such as ANXA1 or its cleavage products, blunting inflammatory responses (and/or with a monoclonal antibody to these, in which an exacerbated inflammatory response was evident) (Vital et al, 2020; Wu et al, 2021; Yang et al, 1997, 1999), exogenous small‐molecule FPR agonists (Borgeson et al, 2015; Brennan, Mohan, McClelland, de Gaetano, et al, 2018; Kain et al, 2017; Petri et al, 2017; Qin et al, 2017; Schottelius et al, 2002) or FPR2‐deficient mice (Chen et al, 2019; Petri et al, 2017; Petri et al, 2018; Tourki, Kain, Pullen, et al, 2020; Tourki, Kain, Shaikh, et al, 2020). Lastly, given the importance of FPR2 in myeloid cell trafficking during infection and inflammation, FPRs could be used to develop novel therapeutic approaches for antibiotic development, as shown by fusion of an antibiotic‐targeting element with an FPR agonist, which enhances neutrophil clearance, providing a viable immunotherapeutic strategy to treat resistant S. aureus infections (Payne et al, 2021).…”
Section: Indications For Fpr2‐targeted Therapiesmentioning
confidence: 99%